Too Many Junctions? A Case Study of Multijunction Thin‐Film Silicon Solar Cells. (22nd September 2017) - Si, Fai Tong; Isabella, Olindo; Zeman, Miro
Abstract: The benefit of two‐terminal multijunction solar cells in regard to the number of junctions (subcells) is critically evaluated. The optical and electrical losses inherent in the construction of multijunction cells are analyzed using information from thin‐film silicon photovoltaics as a representative case. Although the multijunction approach generally reduces the thermalization and nonabsorption losses, several types of losses rise with the number of subcells. Optical reflection and parasitic absorption are slightly increased by adding supporting layers and interfaces. The output voltages decline because of the tunnel recombination junctions, and more importantly of the illumination filtered and reduced by the top subcell(s). The loss mechanisms consume the potential gains in efficiency of multijunction cells. For thin‐film silicon, the triple‐junction is confirmed to be the best performing structure. More generally, only when each component subcell shows a high ratio between the output voltage and the bandgap of the absorber material, a multijunction cell with a large number of subcells can be beneficial. Finally, the high voltage and low current density of multijunction cells with a large number of subcells make them difficult to optimize and manufacture, vulnerable to any changes in the solar spectrum, and thus less practical for the ordinary terrestrial applications. Abstract : Two‐terminal multijunction solar cells trade structure simplicity for conversion efficiency. Several optical and electrical loss mechanisms are critically evaluated as they can drain the benefit obtained from this trade‐off. The losses grow considerably with the number of subcells, limiting the potential of developing many‐junction solar cells.